A comprehensive designation of tailings storage dams – a case study of the sangan iron mine project in Iran - Maleki, Shaho; Khalilidermani, Mitra (Wydawnictwa AGH, 2023)
Tailings storage dams are considered to be one of the most essential facilities in mining projects. In metal mines, after blasting the rocks, the blasted ore is transferred to specific industrial plants for processing operations. During such operations, a large amount of pollutant tailings are inevitably generated. Those tailings must be safely stored in previously constructed storage dams. In this research, a storage dam has been designed to store the tailings of the Iranian Sangan Iron Mine project. The geometry and capacity of the dam were designed to minimize the construction works and to maintain the stability of the facility. To assess the stability of the proposed storage dam, a numerical analysis was performed for both static and dynamic loading conditions. The results showed that the embankment is stable under these two different loading conditions. Hence, the proposed design can be successfully adopted for the construction of a tailings storage dam in the project. In addition, the methodology presented in this research can be used by geotechnic engineers to design safe tailings storage dams in mining projects.
Journal of Geotechnology and Energy
Keywords: tailings dam; waste disposal; mining impacts; numerical modelling; slope stability analysis